2017
DOI: 10.1038/tp.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Striatal phosphodiesterase 10A and medial prefrontal cortical thickness in patients with schizophrenia: a PET and MRI study

Abstract: The enzyme phosphodiesterase 10A (PDE10A) is abundant in striatal medium spiny neurons and has been implicated in the pathophysiology of schizophrenia in animal models and is investigated as a possible new pharmacological treatment target. A reduction of prefrontal cortical thickness is common in schizophrenia, but how this relates to PDE10A expression is unknown. Our study aim was to compare, we believe for the first time, the striatal non-displaceable binding potential (BPND) of the new validated PDE10A liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
(53 reference statements)
0
31
1
Order By: Relevance
“…If the inhibition of PDE10A is indeed a viable treatment option, an increase in striatal PDE10A levels in schizophrenia would be expected. However, we recently found that striatal PDE10A was reduced in patients with schizophrenia compared to controls [11]. Understanding whether and how this relates to changes in brain function in the striatum and its associated symptoms would help to clarify the role of PDE10A in schizophrenia.…”
Section: Phosphodiesterase 10amentioning
confidence: 95%
See 3 more Smart Citations
“…If the inhibition of PDE10A is indeed a viable treatment option, an increase in striatal PDE10A levels in schizophrenia would be expected. However, we recently found that striatal PDE10A was reduced in patients with schizophrenia compared to controls [11]. Understanding whether and how this relates to changes in brain function in the striatum and its associated symptoms would help to clarify the role of PDE10A in schizophrenia.…”
Section: Phosphodiesterase 10amentioning
confidence: 95%
“…The aim of this study was to investigate whether an earlier reported reduction in striatal PDE10A levels [11] relates to striatal function in schizophrenia. The relationship between PDE10A availability and ALFF within the striatum and its basal ganglia output regions was assessed.…”
Section: Striatal Function In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…In a study investigating the role of PDE10A in schizophrenia, 11 C -IMA107 showed no significant difference between patients and HC in any brain region, with all average differences within the variability of the tracer from previous testretest data [282]. In contrast, 11 C-Lu AE92686 showed significantly lower BP ND in the putamen and caudate nucleus compared with that in HC, but no correlation to symptoms was found [142].…”
Section: Disease State Imaging With Pde10a Tracersmentioning
confidence: 82%